INTERAKSI MIGHTY EARTH DENGAN PEMERINTAH PANTAI GADING DALAM KAMPANYE CHOCOLATE’S DARK SECRET TAHUN 2017 - Khrisna, Minanda; Dharmiasih, D.A. Wiwik; Sushanti, Sukma (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL), 2019)
ABSTRACT Interaction between non-governmental organization with government in the environmental issues has been developed in International Relations studies. Deforestation issue in Cote d’Ivoire in 2017 has been taken as a case study in this research. Mighty Earth as international non-governmental organization with its Chocolate’s Dark Secret campaign interacts with the Government of Cote d’Ivoire in 2017. The involving of international chocolate companies as main actor on this issue had taken Mighty Earth’s attention. Therefore, Mighty Earth interacted with Cote d’Ivoire Government to grab those companies attention. The interaction between these 2 actors is proven from the different strategy with the same purpose. This research finds that these two actors used complementary model in their interaction. With applying the descriptive-qualitative methods, this research describes the interaction based on comparative advantages. It is collected from legal sites, online news, academic research, and other related articles. Keywords: Deforestation, Campaign, Complementary Model, Non-Governmental Organization